2017
DOI: 10.1177/1524839917715438
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Experiences of Low-Income Individuals Receiving Farmers’ Market Incentives in the United States: A Qualitative Study

Abstract: The perceived benefits and barriers to shopping at FM and receiving FM incentives should be considered by future programmers and funding agencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 30 publications
2
57
1
Order By: Relevance
“…The program examined by Olsho et al [34], was structured similarly, in that some participants received the incentive through a match after they made a purchase, while others received the incentive from community-based organizations absent of any purchase, usually after they attended a nutrition workshop or other health and fitness program. Similarly, two incentive distribution methods were employed in the program examined by Savoie-Roskos et al [39]; participants received either "regular incentives", which were distributed at regular intervals without any purchase requirement, or matched incentives. Bowling et al [27] employed both POS incentives and tokens; all SNAP recipients shopping at participating markets received a matched incentive when they used their EBT card at these markets, which could not be saved for future use, but at every third market, participants also received $20 in "Bonus Buck" tokens.…”
Section: Delivery and Timing Of Incentive Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The program examined by Olsho et al [34], was structured similarly, in that some participants received the incentive through a match after they made a purchase, while others received the incentive from community-based organizations absent of any purchase, usually after they attended a nutrition workshop or other health and fitness program. Similarly, two incentive distribution methods were employed in the program examined by Savoie-Roskos et al [39]; participants received either "regular incentives", which were distributed at regular intervals without any purchase requirement, or matched incentives. Bowling et al [27] employed both POS incentives and tokens; all SNAP recipients shopping at participating markets received a matched incentive when they used their EBT card at these markets, which could not be saved for future use, but at every third market, participants also received $20 in "Bonus Buck" tokens.…”
Section: Delivery and Timing Of Incentive Benefitsmentioning
confidence: 99%
“…Some programs implemented multiple forms of incentives. For example, Savoie-Roskos et al [39] provided one group of participants with incentive benefits that did not require them to make a purchase and another group with benefits, in the form of spending matches, that augmented the incentive. A comparison of the outcomes between the groups was not reported.…”
Section: Financial Value Of Incentive To Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the CSA model is the most common in our sample, it only appears in 15% of the papers. Farmers' markets, which are one of the most widespread, promoted and funded forms of AFNs [57][58][59], are included in only 13.7% of the papers.…”
Section: Rq2 What Types Of Afns Have Been Studied In Relation To Susmentioning
confidence: 99%
“…Previous research on matching programs has primarily focused on customer impacts and perspectives. Studies have found positive impacts on participating customers, including increased food security, FM use, and fruit and vegetable consumption (Pellegrino et al, 2018;Savoie Roskos, Wengreen, Gast, LeBlanc, & Durward, 2017;Young et al, 2013). While some research has explored the economic benefits to vendors, including an increase in sales and new customers (Lehnerd, Sacheck, Griffin, Goldberg, & Cash, 2018;Mann et al, 2018;Oberholtzer, Dimitri, & Schumacher, 2012), few studies to date have examined vendor perspectives on participation in matching programs.…”
Section: Introductionmentioning
confidence: 99%